CD38 Antibody Daratumumab for the Treatment of Chronic Active Antibody-mediated Kidney Allograft Rejection. Issue 2 (February 2021) - Doberer, Konstantin; Kläger, Johannes; Gualdoni, Guido A.; Mayer, Katharina A.; Eskandary, Farsad; Farkash, Evan A.; Agis, Hermine; Reiter, Thomas; Reindl-Schwaighofer, Roman; Wahrmann, Markus; Cohen, Gerald; Haslacher, Helmuth; et al.
Abstract : Background: Late antibody-mediated rejection (AMR) is a major cause of transplant failure. Potential therapeutic targets are plasma cells and natural killer (NK) cells, both expressing high levels of CD38. Methods: Here, we report the use of CD38 monoclonal antibody daratumumab (9-mo course) in a kidney allograft recipient diagnosed with smoldering myeloma and anti-HLA class II donor-specific antibody-positive chronic active AMR 13 years after transplantation. Patient monitoring included serial HLA single-antigen testing, peripheral blood immune cell phenotyping, as well as follow-up allograft and bone marrow biopsies at 3 and 9 months, including analyses of rejection-related gene expression patterns. Results: Daratumumab led to persistent CD138 + cell depletion in the bone marrow and blood and substantially decreased NK cells counts in blood and graft tissue. At the same time, donor-specific antibody in serum disappeared, and in vitro alloantibody production by CD138 + cells enriched from bone marrow aspirates was abrogated. A 3-month follow-up biopsy revealed a complete resolution of microcirculation inflammation (g+ptc: 3 to 0) and molecular AMR activity (AMR score: 0.79 to <0.2). The same biopsy showed (subclinical) tubulointerstitial inflammation, which prompted steroid treatment. Over an observation period of 12 months, graft function stabilized. Conclusions: Targeting CD38 for plasma cell and NK cell depletion may be an effective strategy to counteract AMR. Our results may encourage the design of future trials to clarify the role of this innovative treatment concept in organ transplantation. Abstract : Supplemental Digital Content is available in the text.